وقف تنفيذ القرار الإداري في حالة الاعتداء الجسيم من الإدارة - بــاسي، جيالني; بري ،اليمين (جامعة الوادي University of El Oued, 2025)
أخضع المشرع الجزائري الإدارة للرقابة القضائية المستعجلة عندما يترتب على إصدارها قراراتها اعتداء جسيم، تحقيقًا للمصلحة العامة، وذلك لحماية الحقوق والحريات الأساسية للأفراد. إلا أن القضاء لا يقبل طلبات وقف تنفيذ هذه القرارات إلا في حالات معينة، إذا كانت أفعالها مخالفة للقانون، مع اتخاذ جميع التدابير اللازمة، بما في ذلك وقف تنفيذ القرار مباشرة تجاه الموجه إليهم. كما يجوز الطعن في جميع الأوامر المستعجلة أمام محاكم الاستئناف أو مجلس الدولة، وذلك بحسب الجهة التي أصدرت القرار. The Algerian legislator has subjected the administration to urgent judicial oversight when it results in a serious assault during the issuance of its decisions in order to achieve the public interest, and this is to protect the basic rights and freedoms of individuals. However, the judiciary does not accept requests to suspend the implementation of these decisions except under certain conditions if its actions violate the law, while taking all necessary measures, including suspending the implementation of the decision directly towards its addressees. It is also possible to appeal all urgent orders before the courts of appeal or the Council of State, depending on the authority that issued the decision.
قانون إداري
Keywords: القضاء المستعجل - دعوى وقف التنفيذ - قرار إداري - الحريات الأساسية; Urgent Judiciary - Suspension of Execution Suit -Administrative Decision - Basic Freedoms